Hubungan Etika Birokrat dengan Pelayanan Pajak Kendaraan Bermotor di Kantor Samsat Palembang - Holipah; Anggleni, Andela (Jurnal Stia Bengkulu : Committe to Administration for Education Quality, 2024)
Law Number 25 of 2009 concerning Public Services is defined as an activity or series of activities in an effort to meet service needs in accordance with laws and regulations for every citizen for goods and services, as well as administrative services provided by public service providers. a government effort to meet the needs of society. The smooth functioning of the general administration and national development is greatly influenced by the perfection of the bureaucrats. To guarantee the achievement of national development goals, bureaucrats who practice ethics, have a good attitude, are neutral, are able to maintain national unity, are professional and responsible in carrying out their duties, ethics in public service are needed as a form of responsiveness from bureaucrats to the interests of society. The purpose of this study was to determine the relationship between bureaucrat ethics and motor vehicle tax services at the Palembang Samsat Office. The research model used is quantitative research with data collection methods using questionnaires and documentation which is carried out systematically based on the research objectives. The sample in this study was 10% of the total population, namely 137 of the 1,370 people/users who pay taxes at the Aceh Besar Samsat office using the incidental method. The analytical method used is validity test, reliability test, normality test, homogeneity test, residual normality test, heterosexuality```` test, simple correlation analysis, analysis of the coefficient of determination and significance test (t test), using the SPSS version 22 application. The results showed that Bureaucratic ethics have a relationship with motor vehicle tax services at the Palembang Samsat office. Evidenced by the large value of the correlation/relationship (R) which is equal to 0.587. Which is then translated through the equation Kd = rxy2 x 100%, so that a coefficient of determination of 34.5% is obtained. Which means, there is a value of 34.5% which has a low closeness relationship, changes in the service variable which are explained through the relationship between bureaucrat ethics. It can be concluded that bureaucratic ethics have a positive relationship with motor vehicle tax services at the Palembang Samsat Office.